2019
DOI: 10.3389/fonc.2019.01287
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Alteration Burden in Advanced Prostate Cancer and Therapeutic Implications

Abstract: The increasing number of patients with sequenced prostate cancer genomes enables us to study not only individual oncogenic mutations, but also capture the global burden of genomic alterations. Here we review the extent of tumor genome mutations and chromosomal structural variants in various clinical states of prostate cancer, and the related prognostic information. Next, we discuss the underlying mutational processes that give rise to these various alterations, and their relationship to the various molecular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 93 publications
(150 reference statements)
1
18
0
Order By: Relevance
“…Mb), which may be somewhat uncertain, given the low tumor content in our case (the complete set of variants are listed in Supplementary Table S3 ), yet a high TMB for primary PCa. It has been estimated that the TMB of unselected and usually treatment-naïve locoregional prostate adenocarcinoma cohorts typically falls between 0.94 and 1.74 nonsynonymous mutations per megabase [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mb), which may be somewhat uncertain, given the low tumor content in our case (the complete set of variants are listed in Supplementary Table S3 ), yet a high TMB for primary PCa. It has been estimated that the TMB of unselected and usually treatment-naïve locoregional prostate adenocarcinoma cohorts typically falls between 0.94 and 1.74 nonsynonymous mutations per megabase [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to the preliminary results of an ongoing trial, PCa patients with tumors having a PD-L1 level of at least 1%, HR deficiency mutations, DNA damage repair mutations, or a TMB greater than the median of 74.5 mutations showed enhanced responses to a combined nivolumab/ipilimumab treatment [ 65 ]. Our subject has signs of HR deficiency (the most dominant mutational signature), an ATM mutation of unknown clinical significance, a BRCA2 fusion transcript that likely reduces full BRCA2 functionality, and a significantly higher TMB than the median for PCa [ 26 ]. BRCA2-altered PCa tumors have been shown to harbor enhanced intra-tumoral immune infiltrates compared to wild-type tumors [ 60 ], suggesting treatment options targeting immune cell modulation [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…While blockade of these checkpoints has led to improved responses and changed the treatment paradigm in malignancies such as melanoma, non-small cell lung cancer (NSCLC), efficacy in prostate cancer remains modest [ 22 , 76 , 77 ]. There have been ongoing efforts to identify predictors of response to immunotherapy, such as PD-L1 expression, tumor mutational burden (TMB), and other mutations such as CDK12 [ 78 , 79 , 80 , 81 ]. One study of tumor tissue from patients with mCRPC revealed that 19% demonstrated high PD-1/PD-L1 immunoexpression [ 82 ].…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%
“…have been uncovered in a significant percentage of metastatic castration-resistance prostate cancer (mCRPC) patients. Defects in these DNA repair genes can increase TMB and neoantigen load potentially predicting response to immunotherapy [ 56 , 57 ]. In a study involving a cohort of 4129 prostate cancer patients 1.8% (74/4129) of patients had POLE/POLD1 mutations.…”
Section: Predictors Of Response To Immune Checkpoint Blockadementioning
confidence: 99%